Polarization: What Do We Know and What Can We Do About It? - Casal Bértoa, Fernando; Rama, José (Frontiers in Political Science, 2021)
Polarization is not new in Europe. Looking at electoral support for extreme political forces after the Second World War, one can observe how polarization has been on the rise since the 1960s. Still, it is in the 1990s, with the thaw of European party systems and the subsequent emergence of (populist) radical parties, that the percentage of votes for anti-political establishment parties reached unprecedented levels. In this article we not only show the general (country-level) picture, but also highlight both the consequences and causes of polarization, proposing at the same time some potential remedies to combat it. Using an aggregate, longitudinal unique dataset, containing 47 European countries across more than 170 years from 1848 to 2020 (Casal Bértoa, 2021; Casal Bértoa and Enyedi, 2021), we try to shed light here on the perils of polarization for the quality of democracy, how traditional political parties are to be blamed, and how we can tackle the problem.